Transcriptional Analysis Reveals Key Genes in the Pathogenesis of Nifedipine-Induced Gingival Overgrowth - Yanqin Ju; Lijuan Huang; Shuwei Wang; Shouliang Zhao (Analytical Cellular Pathology)
Background. Nifedipine-induced gingival overgrowth (NGO) is a multifactorial pathogenesis with increased extracellular matrix including collagen and glycans, inflammatory cytokines, and phenotype changes of fibroblasts. However, the molecular etiology of NGO is not well understood. The objective of this study is to investigate the key genes in the pathogenesis of NGO. Methods. In this study, we examined the proliferation and migration abilities of fibroblasts derived from patients with chronic periodontitis, nifedipine nonresponder gingival overgrowth, gingival overgrowth caused by nifedipine, and healthy normal gingiva. We conducted RNA-Seq on these four groups of fibroblasts and analysed the differentially expressed genes (DEGs). Results. Fibroblasts derived from NGO patients had higher proliferation and migration abilities than those of the other groups. Protein-protein interaction network analysis indicated that TGFB2, ITGA8, ITGA11, FGF5, PLA2G4D, PLA2G2F, PTGS1, CSF1, LPAR1, CCL3, and NKX3-1 are involved in the development of NGO. These factors are related to the arachidonic acid metabolism and PI3K/AKT signaling pathways. Conclusion. Transcriptional gene expression analysis identified a number of DEGs that might be functionally related to gingival overgrowth induced by nifedipine. Our study provides important information on the molecular mechanism underlying nifedipine-induced gingival overgrowth.